2014
DOI: 10.1177/2048872614523348
|View full text |Cite
|
Sign up to set email alerts
|

Favourable 5-year postdischarge survival of comatose patients resuscitated from out-of-hospital cardiac arrest, managed with immediate coronary angiogram on admission

Abstract: OHCA patients undergoing on-admission CA had a very favourable postdischarge survival. Patients with OHCA due to ACS had better survival to discharge at 5-year follow up than patients with OHCA due to other causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…A more recent study by Sideris et al also showed similar survival rates after hospital discharge. 47 Our overall survival after five years was 85% regardless of intervention or rhythm. Combined MTH and PCI has been associated with better in-hospital outcomes in cohort studies.…”
Section: Discussionmentioning
confidence: 70%
“…A more recent study by Sideris et al also showed similar survival rates after hospital discharge. 47 Our overall survival after five years was 85% regardless of intervention or rhythm. Combined MTH and PCI has been associated with better in-hospital outcomes in cohort studies.…”
Section: Discussionmentioning
confidence: 70%
“…3,[26][27][28][29] On the prehospital field and immediately after admission, temperatures were measured with infrared tympanic thermometers. Subsequent temperature measurements were performed for each patient with a bladder probe (Foley urinary catheter with tip thermistor, Tyco Healthcare, Plaisir, France) and/or an esophageal probe (Mon-a-Therm Temperature Probe 400, Covidien, Mansfield, MA; Table I in the online-only Data Supplement).…”
Section: Protocol and Treatmentmentioning
confidence: 99%
“…In a previous study, patients with OHCA due to ACS had better survival to discharge at fiveyear follow up than patients with OHCA due to other causes. 14 Increasing age was an independent predictor of inhospital mortality in our analysis despite contemporary care with PPCI utilising advanced interventional strategies and pharmacotherapies. This finding is consistent with a previous observation that cardiopulmonary resuscitation (CPR) was rarely effective for elderly patients (>70 years of age) with CA that are either out-of-hospital, not witnessed, or associated with asystole or EMD.…”
Section: Discussionmentioning
confidence: 65%
“…In a previous study, patients with OHCA due to ACS had better survival to discharge at five-year follow up than patients with OHCA due to other causes. 14…”
Section: Discussionmentioning
confidence: 99%